Concepts, causes and consequences of trust in news media – a literature review and framework. Issue 2 (3rd April 2021) - Fawzi, Nayla; Steindl, Nina; Obermaier, Magdalena; Prochazka, Fabian; Arlt, Dorothee; Blöbaum, Bernd; Dohle, Marco; Engelke, Katherine M.; Hanitzsch, Thomas; Jackob, Nikolaus; Jakobs, Ilka; Klawier, Tilman; et al.
ABSTRACT: Research on trust in media is on the rise. However, communication scholars have addressed related concepts (e.g. media credibility) for decades, and these concepts have often been used interchangeably with that of trust. This practice has resulted in a confusing field of research, with studies using different labels and drawing on various theoretical backgrounds. This article aims to improve conceptual clarity. On the basis of a literature review, we first propose a broad conceptualization of trust in news media and disentangle it from related concepts. Second, we develop a framework that identifies individual- and societal-level causes and consequences of trust in various media objects. Third, we review the current state of research on social, political, and media-related correlates of trust.